M148 Investigating The Feasibility Of An Online Health Resource With Nurse Coaching To Support Self-management In Copd. (10th November 2014) - Young, J; Early, F; Wisbauer, S; Homan, K; Fuld, J; Tojo, L
Abstract : Introduction: Pulmonary rehabilitation includes self-management support for COPD but is not suitable for or accessible to all. Web based approaches have potential to provide self-management support but effectiveness is not consistently demonstrated and issues of reach and adoption are relatively unstudied. We performed a mixed methods before-and-after study of an intervention comprising web-based health promotion for LTC self-management, The Prevention Plan TM (TPP), with integrated nurse coach support. This report describes the qualitative evaluation. The aim was to understand the benefits gained and the characteristics of patients most likely to benefit. Method: Nineteen patients were recruited in two waves from May 2012–January 2013. Key selection criteria included for group 1 FEV1 < 50% predicted and for group 2 FEV1 <75% predicted. Semi-structured interviews were scheduled for one month and three months after recruitment and were focused around experiences of the programme, benefits and self-management behaviours. Qualitative data were imported into NVivo 10 and analysed through thematic content analysis. Two researchers discussed the themes and subthemes to ensure non-redundant categorization. Results: Fifteen patients were interviewed. Key benefits: increased motivation for self-management, use of self-management skills, increased access to resources and enhanced understanding of lifestyle risk factors. Benefits were facilitated by use of action plans within TPP, nurse coach support to on-going motivation and completion of a health risk assessment by those with little awareness of lifestyle risks. Barriers to gaining benefit included preference for one-to-one contact, insufficient tailoring of website content and difficulties with website navigation. Patients most likely to benefit were those who: wanted to change but had no behavioural strategy; had little previous disease education; had an autonomous sense of self-determination. Conclusions: The programme provided good support for the action phase of behaviour change, but less so for the motivational phase. Patients who were ready to change but did not have knowledge, skills or strategies benefited the most. When implementing a behaviour change programme providers should identify whether it addresses motivation and/or behaviour and assess potential participants accordingly. People who are not ready or able to change may derive little benefit from a behavioural programme.